La lúdica en el aprendizaje de las operaciones básicas matemáticas del Cuarto grado “C” de la Escuela “Teniente Hugo Ortiz” Loja 2021-2022. - Buri Buri, Janeth Maribel (2022)
This research aims to learn about ludic in mathematics in order to reduce the mathematical difficulties presented by students. The general objective was to analyze the ludic as a strategy to improve the teaching-learning of basic mathematical operations of students of the Fourth grade, parallel "C" of the school of General Basic Education "Teniente Hugo Ortiz"; with the purpose of contributing to the development and strengthening of the same. It is based on three specific objectives, the first, to identify the most suitable ludic techniques that contribute to optimize the teaching-learning process of students' basic mathematical operations, as a second, to recognize the learning difficulties that arise in students during the process of teaching basic mathematical operations, and as a third, to develop an educational proposal that helps improve the teaching-learning process of basic mathematical operations. The focus of the present research work had a mixed approach, that is, quantitative-qualitative, which allowed to know and understand the point of view of those involved. The methods used are the documentary, descriptive, analytical and synthetic; likewise techniques such as direct observation and the survey were used to know the feasibility of the work, therefore, the ludic is a methodological strategy to teach and learn differently, the incorporation of games into mathematics will favour the student’s participation against the difficulties presented in learning such as dyscalculia, acalculia, distraction in the classroom, the way in which it is taught, lack of support and motivation, negative attitude, disinterest to learn, therefore, a didactic guide was developed for the different recreational activities, its importance is to contribute with learning resources that optimize the development of the teaching and learning process of students. Keywords: ludic, basic math operations, learning difficulties, game, learning.